Silver Nanoparticle-Based Dressings for Various Wounds: Benefits and Adverse Effects - Korapin Phatanodom; Chayanin Angthong (Polish Journal of Surgery, 2022)
BACKGROUND: Silver nanoparticles (AgNP) are a novel therapeutic approach to wound dressings because of their antibacterial properties. Silver has been used throughout history for many purposes. However, evidence-based information about the benefits of AgNP-based wound dressings and potential adverse effects is still required. This study is to comprehensively review the benefits and complications of AgNP-based wound dressings for different wound types and address the knowledge gaps. MATERIAL AND METHODS: We collected and reviewed the relevant literature from available sources. RESULTS: AgNP-based dressings have antimicrobial activity and promote healing with only minor complications, making them suitable for several types of wounds. However, we could not identify any reports on AgNP-based wound dressings for common acute traumatic wounds, such as lacerations and abrasions; this includes comparative studies of AgNP-based and conventional wound dressings for such wound types. CONCLUSIONS: AgNP-based dressings benefit traumatic, cavity, dental, and burn wounds with only minor complications. However, further studies are needed to discern their benefits for specific traumatic wound types.
Keywords: Wound Healing and Treatments; Nanoparticles: synthesis and applications; Graphene and Nanomaterials Applications